Widespread Cortical Thickness Is Associated With Neuroactive Steroid Levels - Morey, Rajendra A.; Davis, Sarah L.; Haswell, Courtney C.; Naylor, Jennifer C.; Kilts, Jason D.; Szabo, Steven T.; Shampine, Larry J.; Parke, Gillian J.; Sun, Delin; Swanson, Chelsea A.; Wagner, Henry R.; , Mid-Atlantic MIRECC Workgroup; et al. (Frontiers in Neuroscience, 2019)
Background: Neuroactive steroids are endogenous molecules with regenerative and neuroprotective actions. Both cortical thickness and many neuroactive steroid levels decline with age and are decreased in several neuropsychiatric disorders. However, a systematic examination of the relationship between serum neuroactive steroid levels and in vivo measures of cortical thickness in humans is lacking. Methods: Peripheral serum levels of seven neuroactive steroids were assayed in US military veterans. All (n = 143) subsequently underwent high-resolution structural MRI, followed by parcellelation of the cortical surface into 148 anatomically-defined regions. Regression modeling was applied to test the association between neuroactive steroid levels and hemispheric total gray matter volume as well as region-specific cortical thickness. False discovery rate (FDR) correction was used to control for Type 1 error from multiple testing. Results: Neuroactive steroid levels of allopregnanolone and pregnenolone were positively correlated with gray matter thickness in multiple regions of cingulate, parietal, and occipital association cortices (r = 0.20 to 0.47; p<0.05; FDR-corrected). Conclusions: Positive associations between serum neuroactive steroid levels and gray matter cortical thickness are found in multiple brain regions. If these results are confirmed, neuroactive steroid levels and cortical thickness may help in monitoring the clinical response in future intervention studies of neuroregenerative therapies.